Histopathological differentiation of skin lesions caused by electrocution, flame burns and abrasion - (:unkn) unknown (ELSEVIER IRELAND LTD, 2008)
The aim of this study was to reveal histopathological features for differential diagnosis of skin lesions caused by electrocution, flames and abrasions. Based on the causes of the lesions, cases were assigned into three groups. Group I included 30 deaths from electric shock. Group 2 included 30 individuals with flame burns who died in the fires. Group 3 included 30 deaths from traffic accidents, from which the individuals had abrasions. Data from the crime scene investigations and macroscopic and microscopic findings from the autopsies allowed determination of the cause of death in all cases. The features of the lesions examined under the light microscope were intraepidermal separation, subepidermal (dermoepidermal) separation, coagulation necrosis in the epidermis, nuclear elongation in the epidermis, dark-staining epidermal nucleus, depth of homogenization in the dermis, and nuclear elongation in the epithelium of hair follicles. A significantly high rate of electrical lesions had intraepidermal separation. The rate of subepidermal separation was slightly more significant in flame burns. A significantly higher rate of electrical lesions had both intraepidermal and subepidermal separation. The rate of coagulation necrosis in the epidermis was significantly the highest in electrical lesions. Although the severity of nuclear elongation was the most significant in electrical lesions, varying degrees of nuclear elongation in the epidermis were present in all three groups. Dark staining of the epidermal nuclei was present in all lesions except for one electrical lesion, though the severity of staining was significant in the abrasion group. The depth of homogenization was slightly more significant in the abrasion group. The rate of nuclear elongation in the epithelium of the hair follicles was significantly lower in the abrasion group. The results of this study revealed that certain morphological changes determined under a light microscope could help the differential diagnoses of electrical lesions, flame burns and abrasions. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: electrocution; histopathological features; forensic autopsy; INJURED PIG SKIN; EPIDERMAL CHANGES; HEAT